2010
DOI: 10.1371/journal.pone.0009289
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Resource of Interacting Protein Regions for Refining Human Transcription Factor Networks

Abstract: Large-scale data sets of protein-protein interactions (PPIs) are a valuable resource for mapping and analysis of the topological and dynamic features of interactome networks. The currently available large-scale PPI data sets only contain information on interaction partners. The data presented in this study also include the sequences involved in the interactions (i.e., the interacting regions, IRs) suggested to correspond to functional and structural domains. Here we present the first large-scale IR data set ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 57 publications
(121 reference statements)
1
56
0
Order By: Relevance
“…This analysis revealed that ETS1 could bind to the histone de-acetylation-related molecule HDAC1 and that ELK1 could bind to the DNA methylation-related molecule ARID4B 28,29 (Supplementary Fig. 9a).…”
Section: Resultsmentioning
confidence: 97%
“…This analysis revealed that ETS1 could bind to the histone de-acetylation-related molecule HDAC1 and that ELK1 could bind to the DNA methylation-related molecule ARID4B 28,29 (Supplementary Fig. 9a).…”
Section: Resultsmentioning
confidence: 97%
“…The identification of one network, including NKX2.5/GATA4, provided a robust positive control as protein-protein interactions and substantial contributions by these molecules to CHD are previously described. Direct protein-protein interactions between ETS1/JUN/TOP2A have also been reported, 54-56 but this network has not been previously implicated in CHD. In an expanded network analysis of these molecules that included rare LOF mutations identified from exome sequencing, JUN was linked to SMAD2 and SMAD4, molecules that participate in cardiac development through the TGF-β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…p53 by interfering with its murine double minute 2 (MDM2)-dependent proteasomal degradation (13), and there is evidence for an interaction between PRRC2C and MDM2 (48). The role of the PRRC2C splice variants in the regulation of p53 by MDM2 merits further investigation.…”
Section: Discussionmentioning
confidence: 99%